Prototyping a scalable smart village (B) - Darwin, Solomon (SAGE Knowledge. Cases., 2018)
This case focuses on the development of Smart Villages in the state of Andhra Pradesh (AP), India. The case study allows students to consider how to overcome economic, cultural and political obstacles in order to engage in Open Innovation that inevitably leads to wealth creation and greater happiness. The directors of Smart Villages must find a way to encourage investment and effect a cultural shift while navigating deeply entrenched but ineffective present systems.